Role of iron conditioners on organics evolution in overall process of sludge hydrothermal carbonization followed by pyrolysis. (October 2022) - Mu, Kai; Zhang, Qiang; Luo, Guangqian; Han, Jun; Qin, Linbo; Zhao, Bo; Chen, Wangsheng; Yi, Linlin
Abstract: Iron compounds were widely used for sludge dewatering, which may do work in the following process of sludge disposition. Considering that hydrothermal pre-treatment accompanied with pyrolysis was a promising rote for sludge resourceful utilization, the dually catalytic effects of different iron conditioners on organics conversion in both phases were investigated in this study. The results showed that iron conditioners reduced hydrothermal temperature and time to prepare high quality hydrochar. Specifically, FeCl3 accelerated the aliphatics conversion into aromatics and FeSO4 tended to fix partial carbon in solid product. After hydrothermal carbonization, 50%∼86% Fe2 O3 remained in hydrochar and then promoted organics thermal decomposition by catalytic oxygenolysis. Although 62–91% iron from FeCl3 and FeSO4 dissolved in hydrothermal liquid, the catalytic action on hydrochar pyrolysis was more obvious, leading to lower reaction order and activation energy. Besides, the residual iron in hydrochar from FeCl3 reduced with hydrothermal temperature and time, while iron distribution kept stable for FeSO4 . In comparison, FeSO4 conditioner was more suitable for sludge thermal disposal. The hydrochar with high carbon content and reactivity could be received in the economical way. Graphical abstract: Image 1